Retrospective epidemiology of the SARS-CoV-2 (and COVID-19) epidemic among 27 Brazilian cities - Sandra Souza Lima (Elsevier, 2021)
Background: Most of the countries facing the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic are still trying to understand the dynamics of the behavior of the virus and dissemination of the new agent. Objectives: A retrospective descriptive epidemiological study of the 26 state capitals of Brazil and its capital, Brasilia, was performed to investigate the behavior of the infection and disease caused by SARS-CoV-2. Study design: The data presented were obtained from the State Health Departments and the Brazilian Ministry of Health. Seven epidemiological markers (including the incidence, mortality and case fatality rates and the growth of the epidemic measured by the ratios observed on days 30, 60 and 90) were compared for the initial 90 days of the epidemic for each city. Results: The epidemic spread to the country within 25 days, and deaths occurred as early as nine days from initiation. The incidence and mortality rates ranged from 70 to almost 1,599/100,000 and less than 1 to 1,171/1,000,000, respectively, at the end of the 90-day period of observation. The CFR was less than two up to 12.31%. The magnitude of each marker clustered the cities in different groups. The epidemic was managed differently in each city, with differences in qualified medical services and medical preparedness to face the emergency situation. Conclusions: Although modeling the epidemic has been a constant task, epidemiological data should be pursued to define actual information, such as the prevalence and incidence rates, to understand the unpredictable nature of this emerging infection, including the present policy of vaccination campaigns.